Analysis of Strategic Factors Affecting the Success of Small Enterprises in South Sulawesi - Fitriany, Fitriany; Abidin, Zainal (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2018)
The purpose of the present study is to analyse the effect of managerial competence, information access on cost, benefit differentiation of small business products. This research is done in five district in South Sulawesiâ€” Makassar, Maros, Bantaeng, Bulukumba and Tanah Toraja. The populations of this study are owners and managers of food and beverage business, wood and rattan furniture, convection and apparel. The sample was chosen purposively for 170 responders. Survey and questionnaire were used in data collection. Then the data were analysed descriptively and structural equation model with AMOS (Analysis of moment structural) program.The results of the study show that the success of small-scale enterprises is directly influenced by strategic factors, namely managerial competence, information access, and product differentiation. The factors of negative cost advantage but significant influence the success of the business because customers prefer the uniqueness. If small entrepreneurs in South Sulawesi want to succeed, then it should pay attention to the factor of product differentiation superiority because the influence is big enough and significant to the success of small business. This identifies that small business products should be more unique in terms of more value than a cheaper price.Keywords: Manager's Competence, Access to Information, Cost Advantage, Â Advantage of Deferment, Business Success.